PENGARUH PERCEIVED QUALITY, BRAND AWARENESS, BRAND IMAGE TERHADAP BRAND LOYALTY DALAM INDUSTRI PERBANKAN SYARIAH - NUNO SUTRISNO; SATRIA NURRAHMAT (Media Bisnis, 2020)
The purpose of this study was to determine the effect of Perceived Quality, Brand Awareness, Brand Image on Brand Loyalty at Bank Muamalat in DKI Jakarta. The research method used in this research is through a survey. The data were analyzed quantitatively and used a causal research design. The sampling method used in this study is to use Non-Probability Sampling with purposive sampling technique. All sample data obtained by distributing questionnaires totaled 113 respondents and will be processed using SPSS 23 software. The data analysis technique used in this research is multiple linear regression. The results of this study indicate that Perceived Quality, Brand Awareness and Brand Image have an influence on Brand Equity. This research is expected to provide input or suggestions to Islamic Banking, especially Bank Muamalat which is the object of this research, in order to increase its market share in the Islamic banking industry in Indonesia.